IDENTIFIKASI DINI SISWA LOW VISION DI SEKOLAH DASAR: HASIL SKRINING DAN IMPLIKASINYA TERHADAP LAYANAN PENDIDIKAN INKLUSIF - M. Irfandi; M. Khairul Lutfi; Abdul Khair (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Visual impairment in school-aged children often remains undetected despite its substantial impact on learning and overall academic development. This study aims to map the functional vision of elementary school students through a structured visual screening using the Functional Residual Vision Assessment (ASF). A descriptive quantitative approach with a field-study design was employed, involving all students at SDN 1 Teros through a total sampling technique. The screening assessed multiple components of functional vision, including light response, contrast sensitivity, near–far vision, visual field use, visual tracking and scanning, focus shifting, eye–hand coordination, and the ability to read large print materials. The results indicate that 11.86% of students showed signs of visual impairment, with 5.08% categorized as having indications of low vision. Students identified with visual difficulties demonstrated compensatory behaviors such as difficulty following visual instructions, slower copying from the board, and avoidance of reading activities. Notably, none of these students had previously undergone formal visual examinations, highlighting the absence of early identification mechanisms in the school. These findings emphasize the necessity of implementing regular visual screening, adapting classroom strategies to support visual access, and strengthening collaboration among schools, parents, and eye-health professionals to ensure inclusive and equitable learning opportunities.